2016
DOI: 10.1159/000448250
|View full text |Cite
|
Sign up to set email alerts
|

Sedation for Bronchoscopy and Complications in Obese Patients

Abstract: Background: Bronchoscopy is a safe and minimally invasive diagnostic tool, but no studies have reported prospectively on sedation and outcomes in patients with objectively defined obesity. Objectives: The purpose of the study is to determine if obese patients require more sedation or had more procedural complications during bronchoscopy under moderate sedation than non-obese patients. Methods: We evaluated complications and sedation requirements in non-obese versus obese patients, defined by multiple criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…The literature on outcomes of conscious sedation among obese women is limited. Our observation of an increase in fentanyl and midazolam dose associated with increasing BMI is in keeping with two studies of other procedures using conscious sedation including bronchoscopy and firsttrimester surgical abortion (11,12). Similarly, an increase in propofol dose has been observed with increasing BMI in endoscopy under deep sedation (13), as well as OPUs for IVF under total intravenous anesthesia (9).…”
Section: Discussionsupporting
confidence: 88%
“…The literature on outcomes of conscious sedation among obese women is limited. Our observation of an increase in fentanyl and midazolam dose associated with increasing BMI is in keeping with two studies of other procedures using conscious sedation including bronchoscopy and firsttrimester surgical abortion (11,12). Similarly, an increase in propofol dose has been observed with increasing BMI in endoscopy under deep sedation (13), as well as OPUs for IVF under total intravenous anesthesia (9).…”
Section: Discussionsupporting
confidence: 88%
“…In another study by Khan et al ., they did not find any clinically significant difference in sedation needs or an increase in complications in obese versus nonobese patients. [22] The association between anxiety and obesity is contradicting. [23] There is moderate evidence that shows obesity is positively associated with anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The few existing studies of Mallampati score for procedural sedation are inadequate and inconclusive. 22,[44][45][46] In their most recent procedural sedation policy, the American College of Emergency Physicians (ACEP) concluded that "[t]here is no evidence that the addition of the Mallampati score to a standard general evaluation of the anatomic or physiologic variants.has any impact on clinical outcomes during sedation, and thus it cannot be recommended." 61 In conclusion, the literature evidence demonstrates that the Mallampati score is inadequately sensitive for the identification of difficult laryngoscopy, difficult intubation, and difficult bag-valve-mask ventilation, with likelihood ratios indicating a small and clinically insignificant effect on outcome prediction.…”
Section: Discussionmentioning
confidence: 99%